2011
DOI: 10.1093/cid/ciq073
|View full text |Cite
|
Sign up to set email alerts
|

Cranberry Juice Fails to Prevent Recurrent Urinary Tract Infection: Results From a Randomized Placebo-Controlled Trial

Abstract: Overall, the recurrence rate was 16.9% (95% confidence interval, 12.8%-21.0%), and the distribution of the recurrences was similar between study groups, with the active cranberry group presenting a slightly higher recurrence rate (20.0% vs 14.0%). The presence of urinary symptoms at 3 days, 1-2 weeks, and at ≥ 1 month was similar between study groups, with overall no marked differences. CONCLUSIONS.: Among otherwise healthy college women with an acute UTI, those drinking 8 oz of 27% cranberry juice twice daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
119
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(127 citation statements)
references
References 25 publications
2
119
0
6
Order By: Relevance
“…23 BarbosaCesnik et al 23 used a more frequent dosing regimen and studied a larger sample of predominantly college-age women. The major difference was in the definition of the primary outcome, symptomatic UTI, which in the study by Barbosa-Cesnik et al required culture confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…23 BarbosaCesnik et al 23 used a more frequent dosing regimen and studied a larger sample of predominantly college-age women. The major difference was in the definition of the primary outcome, symptomatic UTI, which in the study by Barbosa-Cesnik et al required culture confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…While Jepson et al 47 in their Cochrane Review concluded that there was no evidence for cranberries to prevent UTI, Wang et al 48 found a weak evidence after having excluded one trial as a negative outlier. 49 However, critics rightly argued that this maneuver had caused a bias, as data from a positive outlier study had still been analyzed. 50 Investigators eager to explain negative outcomes of their trials had pointed to unexpectedly low UTI recurrence rates within the chosen observation periods and/or underdosing of the putative active principle.…”
Section: The Mixed Evidence From Clinical Trialsmentioning
confidence: 99%
“…Dette avviker fra tidligere systematiske gjennomganger, der man har funnet en viss effekt av tranebaer. Endringen skyldes inklusjon av en rekke nye studier, ikke minst en stor studie som ble publisert i 2011 og som ikke kunne påvise noen effekt (12).…”
Section: Hva Viser Studiene?unclassified